Preparation method of high-strength heterostructure FeMnCoCrAl series high-entropy alloy

By using short-term insulation and medium-temperature annealing processes in FeMnCoCrAl system high-entropy alloys, the grain coarsening, oxidation and crack problems in the alloy after traditional hot rolling treatment are solved, and a multi-dimensional heterostructure with high strength and good plasticity is achieved.

CN119685567APending Publication Date: 2025-03-25TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411839019.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

After traditional hot rolling treatment, existing high-entropy alloys often experience microscopic and macroscopic defects such as grain coarseness, dendrites segregation, severe oxidation on the surface of the sheet and cracks, which limits their performance.

Method used

A short-term insulation and temperature rolling process slightly higher than the recrystallization temperature and a medium-temperature annealing process close to the recrystallization temperature were prepared to produce a FeMnCoCrAl-based high-entropy alloy with multiple dimensions, avoiding grain coarsening and other defects.

Benefits of technology

Through this process, the alloy obtains higher strength and plasticity, avoids oxidation and cracks on the surface of the sheet, and significantly improves the mechanical properties and processing properties of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685567A_ABST
    Figure CN119685567A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength heterostructure FeMnCoCrAl series high-entropy alloy, and belongs to the technical field of high-entropy alloy preparation. A multi-heterogeneous composite structure with two phases or multiple phases is prepared through forging and pressing, warm rolling and heat treatment annealing processes on the FeMnCoCrAl series high-entropy alloy. Warm rolling adopts a short-time heat preservation rolling process which is slightly higher than the recrystallization temperature, and is matched with a medium-temperature annealing process which is close to the recrystallization temperature, so that a heterogeneous structure which covers multiple dimensions such as grain size, form, recrystallization degree and multiphase layering is constructed. According to the invention, the violent oxidation phenomenon on the surface of the rolled plate is obviously reduced, and the surface cracking phenomenon is greatly reduced. Experimental results show that the strength of the prepared alloy is remarkably enhanced, and meanwhile good strength and plasticity matching is kept. The invention provides a new process scheme and technical support for high-efficiency and low-cost processing of the high-entropy alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy alloy material preparation, and specifically relates to a method for preparing a high-strength heterostructure FeMnCoCrAl series high entropy alloy. Background Art

[0002] High entropy alloys (HEAs) have become one of the focuses of contemporary metal material science research due to their complex element composition and ratio, as well as various preparation processes, showing a series of excellent performance characteristics. In particular, metastable high entropy alloys, due to their diversified phase composition and the ability to trigger a variety of microscopic deformation mechanisms during strain, such as the transition from a metastable phase to another crystal structure phase, make these alloys exhibit excellent mechanical properties at room temperature, low temperature, and even high temperature conditions. Based on this, by optimizing the thermomechanical processing process, a wider range of heterogeneous structural concepts can be incorporated into the model alloy, covering aspects such as grain size, morphology, degree of recrystallization, and the type and distribution of precipitated phases. Furthermore, the balance between strength and plasticity can be regulated to significantly improve the comprehensive mechanical properties of the alloy.

[0003] Chinese patent document (application number: 202210293260.7) discloses a chemical formula of Al x (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x (8≤x≤16at.%) TRIP-assisted FeMnCoCrAl three-phase heterogeneous high entropy alloy, after forging, hot rolling and annealing, the alloy presents a mixed microstructure of face center cubic (FCC), body center cubic (BCC) and hexagonal close packed (HCP) crystal structures. Based on the basic toughness of the three-phase structure of stable FCC soft domain, BCC hard domain and a small amount of HCP hard domain, the alloy has a significant improvement in mechanical properties due to the TRIP (transformation-induced plasticity) effect of the activated metastable FCC phase to HCP phase transformation under strain.

[0004] However, after the traditional hot rolling treatment at over 900°C, these high entropy alloys often show obvious microstructural defects such as grain coarsening and dendrite segregation. The surface of the plate is severely oxidized and fine cracks appear, which brings challenges to subsequent processing and application. The thermomechanical processing technology of traditional high entropy alloys restricts the performance of this alloy to a certain extent. Whether more diverse heterogeneity can be introduced into the alloy microstructure by optimizing the processing technology still needs to be further explored. This topic is of great significance for the enrichment of processing methods and in-depth exploration of performance in the development of new alloys. More importantly, exploring simpler and more cost-effective processing technologies is particularly critical for promoting the development of high entropy alloys, and it is also of far-reaching significance for energy conservation and emission reduction and promoting the sustainable development of the materials industry. Summary of the invention

[0005] The main purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a high-strength heterogeneous structure FeMnCoCrAl series high entropy alloy. Through a short-time heat preservation warm rolling process slightly higher than the recrystallization temperature and a medium-temperature annealing process close to the recrystallization temperature, it is intended to avoid microscopic and macroscopic defects such as grain coarsening, dendrite segregation, and severe oxidation and cracking of the plate surface after alloy processing, thereby obtaining a multi-dimensional heterogeneous structure including grain size, morphology, degree of recrystallization, and multi-phase stratification. Common FeMnCoCrAl series high entropy alloys are composed of FCC and BCC two or even multiple phases. The setting of rolling temperature and heat preservation time reduces the driving force and nucleation size of the two-phase recrystallization, refines the lamellar structure, and obtains different grain sizes, morphologies, and degrees of recrystallization. Fine FCC austenite grains can withstand greater strains, while small-sized BCC grains are easier to accommodate dislocations than large-sized states. The setting of annealing temperature and time can retain the uniform fine grains and refined layered structure formed after warm rolling, promote short-distance atomic diffusion, reduce dislocation density, and repair lattice distortion. The complete process achieves a significant improvement in the strength of the alloy through the fine grain strengthening mechanism of the soft domain, the dislocation strengthening mechanism of the hard domain, and the heterogeneous strain-induced stress mechanism between the soft and hard domains, while maintaining a good match between strength and plasticity.

[0006] The present invention is achieved through the following technical scheme: a preparation method of a high-strength heterostructure FeMnCoCrAl series high entropy alloy, using a short-time heat preservation warm rolling process slightly higher than the recrystallization temperature and a medium-temperature annealing process close to the recrystallization temperature to treat the FeMnCoCrAl series high entropy alloy, to obtain a multi-dimensional heterogeneous structure including grain size, morphology, recrystallization degree and multi-phase stratification, comprising the following steps: S1. Forging: forging the cast FeMnCoCrAl high entropy alloy raw material to obtain a forging blank; S2, warm rolling: heating the forging blank prepared in step S1 to 550°C-850°C, holding the temperature for 10 min-30 min, and then warm rolling the forging blank, wherein the rolling of the forging blank adopts a multi-pass, small deformation rolling method, the rolling path is in the length direction, the reduction rate of each pass is 10%-25%, and the total reduction rate is 50%-90%. After warm rolling, the forging blank is water quenched to obtain a warm rolled plate; S3, heat treatment: the warm rolled sheet prepared in step S2 is subjected to medium temperature annealing, the annealing temperature is 400°C to 800°C, and the holding time is 3 min to 1 h, so as to obtain a high-strength heterostructure FeMnCoCrAl series high entropy alloy.

[0007] Furthermore, the chemical formula of the FeMnCoCrAl high entropy alloy is (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x Al x , 8≤x≤16; or in (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x Al x An FeMnCoCrAl high entropy alloy composed of interstitial elements of C, N, O and B added to a matrix, wherein the atomic percentage of the added interstitial elements of C, N, O and B is not greater than 5 at.%.

[0008] Further, the (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x Al x The high entropy alloy is composed of at least two phases of FCC, BCC, HCP, B2, L12, L21, and Laves phases, and the content of a single phase is 1% to 99%.

[0009] Furthermore, in step S1, the cross-section of the FeMnCoCrAl-based high entropy alloy forging billet is a rectangle.

[0010] Furthermore, in step S2, the thickness of the obtained warm-rolled plate is 10 mm to 30 mm.

[0011] Furthermore, in step S3, the warm rolled plate heat treatment annealing adopts a vacuum atmosphere furnace, and the vacuum degree in the heat treatment furnace is pumped to 10 -3 Below Pa, introduce pure argon gas, then use a vacuum pump to evacuate, and introduce pure argon gas again, and alternately cycle to introduce pure argon gas for at least 3 times.

[0012] Further, in the step S3, the grain morphology of the prepared high-strength heterostructure FeMnCoCrAl high-entropy alloy includes subgrains, equiaxed grains, and striped grains. The grain size range is: subgrain diameter is ≤1 μm, equiaxed grain diameter is 1~100 μm, and striped crystal length is 0.5~100 μm. The degree of recrystallization includes: analyzing and calculating the average orientation inside the grain by electron backscattered diffraction (EBSD) grain orientation spread (grain orientation spread, GOS), and specifying an orientation difference of 1°~2° as a standard for recrystallized grain determination, that is, grains with an orientation difference less than this range are regarded as fully recrystallized grains. The yield strength of the prepared high-strength heterostructure FeMnCoCrAl high-entropy alloy is 600 MPa~1200 MPa, the tensile strength is 650 MPa~1300 MPa, and the elongation is 5%~50%.

[0013] The beneficial effects of the present invention are: 1. The present invention adopts short-time heat preservation and warm rolling for processing, which can effectively alleviate the severe oxidation of the plate surface caused by traditional long-time high-temperature heat preservation and hot rolling; 2. The temperature range of heat preservation and rolling adopted by the present invention can obtain more soft FCC phases, so that the alloy as a whole can withstand higher strain, facilitate rolling, and avoid cracking on the surface of the plate; 3. The processing technology of the present invention is used to process FeMnCoCrAl series high entropy alloys to obtain a heterogeneous grain morphology of long strips + equiaxed crystals; more dislocations are retained in the hard phase to improve the strength of the hard phase; the soft grains are refined to achieve a dual improvement in strength and plasticity; the soft and hard phases synergistically improve the strength of the alloy.

[0014] 4. Compared with the traditional hot rolling and high temperature annealing process, the short-time heat preservation, warm rolling and medium temperature annealing process adopted by the present invention can reduce the processing temperature and time, thus achieving the effect of energy saving, emission reduction and cost reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more intuitively and clearly demonstrate the microstructure, properties and beneficial effects of the alloy after the process of the present invention, the following drawings are provided for illustration and introduction.

[0016] Figure 1 After 800℃ warm rolling (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Actual photo of the surface of Al9(at.%) high entropy alloy plate, with no cracks on the surface of the plate; Figure 2 After hot rolling at 900℃ (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Actual photo of the surface of Al9(at.%) high entropy alloy plate, with cracks and defects on the surface of the plate; Figure 3 (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Microstructure morphology of Al9(at.%) high entropy alloy after 800℃ warm rolling + 550℃ annealing (hereinafter referred to as WR800-AN550); Figure 3 Among them, (a) is the inverse pole figure, (b) is the phase distribution diagram, (c) is the GOS+contrast (BC) diagram of the FCC phase, and (d) is the GOS+BC diagram of the BCC phase; Figure 4 (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Microstructure morphology of Al9(at.%) high entropy alloy after 900℃ hot rolling + 550℃ annealing (hereinafter referred to as HR900-AN550); Figure 4 In the figure, (a) is the inverse pole figure, and (b) is the phase distribution diagram; Figure 5 After 800℃ warm rolling + 550℃ annealing and 900℃ hot rolling + 550℃ annealing (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Comparison of mechanical properties and back stress of Al9(at.%) high entropy alloy; Figure 5 In the figure, (a) is the engineering stress-strain curve, (b) is the true stress-true strain curve of cyclic loading, (c) is the local enlarged view of the WR800-AN550 sample curve in Figure (b), and (d) is the curve of heterogeneous strain induced (HDI) stress changing with true strain. DETAILED DESCRIPTION

[0017] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Example 1

[0018] A method for preparing a high-strength heterostructure FeMnCoCrAl series high entropy alloy comprises the following steps: S1, forging: In this embodiment 1, (Fe 50 Mn30 Co 10 Cr 10 ) 91 Al9 (at.%) high entropy alloy ingot, with a mass of 16 kg, is forged into a square billet with a cross-sectional shape and size of 100 mm in width and 15 mm in thickness, and air-cooled to room temperature to obtain a forged billet; S2, warm rolling: a portion or a section of the forging blank prepared in step S1 is heated to 850°C, and the holding time is 10 min; then warm rolling is performed, and 5 passes of hot rolling are performed using a φ450 mm two-roll reversible high-strength hot rolling mill, the initial rolling temperature is 800°C, and the thickness of the forging blank is hot rolled from 15 mm to 2 mm, and after warm rolling, the forging blank is water quenched and cooled to obtain a warm rolled plate; The warm rolled plate was stretched at room temperature. According to ASTM E8 / E8M, the warm rolled annealed alloy plate was processed into a tensile specimen with a gauge length of 25 mm and a width of 6 mm by wire cutting along the rolling direction. The surface of the specimen was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimen was tested with a strain rate of 10 -3 s -1 Finally, the tensile data is processed and the engineering stress-strain curve is drawn. Figure 5 As shown in the middle figure (a), the yield strength of the warm-rolled plate is 793 MPa, the tensile strength is 846 MPa, and the elongation is 17.5%; S3, heat treatment: anneal the warm rolled sheet prepared in step S2, using a vacuum box atmosphere furnace, model KSXL-1308C, and first evacuate to 10 -3 Pa, pure argon is introduced, and then vacuum is drawn with a vacuum pump, and pure argon is introduced again. Pure argon is introduced three times in an alternating cycle to ensure that a pure argon atmosphere is formed in the furnace chamber. The annealing temperature is 550℃, and the holding time is 3 min. After the holding period, quenching and cooling are performed to obtain a warm rolled annealed high-strength heterostructure FeMnCoCrAl high-entropy alloy.

[0019] The alloy was microstructured by electron back-scattered diffraction (EBSD). Wire cutting was used to cut samples of the warm-rolled annealed state of the high-entropy alloy into a size of 10 × 10 × 2 mm. 3 The block was mechanically ground with 240#, 400#, 800#, 1000#, 1500#, 2000#, and 3000# sandpaper in sequence, and then electrolytically polished with 1:15 perchloric acid alcohol solution to remove the stress layer.

[0020] The EBSD analysis results of the warm-rolled and annealed alloy are as follows Figure 3 shown. The sample is mainly composed of two phases, FCC and BCC, and the two phases are micron-scale layered and evenly distributed. Among them, the proportion of the FCC phase is 64.7%, and only a small amount of the HCP phase exists at the FCC-BCC phase boundary (as shown in Figure 3 Figure (b) in the middle figure). In the FCC phase region, the grains are mainly composed of the following types: a small amount of recrystallized equiaxed grains (GOS < 2.7°, accounting for 4.5%), a large number of medium-sized and relatively thick moderately deformed grains (2.7° < GOS < 10.8°, accounting for 88.3%), and a small amount of severely deformed grains in thin lamellae (GOS > 10.8°, accounting for 7.2%). The BCC phase region includes a large number of small-sized recrystallized grains (0.46 μm, GOS < 2.8°, accounting for 26.4%), a large number of moderately deformed grains (2.86 μm, 2.4° < GOS < 11.3°, accounting for 66.4%), and a small number of severely deformed grains with a grain size slightly larger than the recrystallized grains (GOS > 11.3°, accounting for 7.3%). As the hard phase, the degree of deformation of the BCC phase is significantly less than that of the FCC phase, and more deformation occurs in medium-sized grains.

[0021] The warm-rolled and annealed sample prepared in Example 1 was subjected to tensile testing at room temperature. According to ASTM E8 / E8M, the warm-rolled and annealed alloy plate was processed by wire electrical discharge machining along the rolling direction into a tensile specimen with a gauge length of 25 mm and a width of 6 mm using wire cutting. The surface of the specimen was polished with 400# and 800# sandpapers to remove the oxide layer, prevent slippage between the clamping end and the fixture during the tensile process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimen was subjected to tensile testing at a strain rate of 10 -3 s -1 , and finally the tensile data was processed and the engineering stress-strain curve was plotted.

[0022] Figure 5 Figure (a) in the middle figure is the engineering stress-strain curve of the warm-rolled and annealed alloy under tensile testing at room temperature. The yield strength of the warm-rolled and annealed alloy is 937 MPa, the tensile strength is 994 MPa, and the elongation is 13.0%. At the same time, the warm-rolled and annealed sample was subjected to a loading-unloading-reloading (LUR) test to evaluate the hetero-deformation induced (HDI) stress. The true stress-true strain curves are as shown in Figure 5 Figure (b), Figure (c), and Figure (d) in the middle figure. The sample exhibits obvious HDI stress, which indicates that the HDI hardening generated by the interaction between the hard and soft domain strains provides an obvious strengthening effect. Therefore, the strength and plasticity of the alloy after warm rolling and annealing are improved to varying degrees, and the warm-rolled and annealed sample has better performance in the cyclic loading test. Example 2

[0023] A method for preparing a high-strength heterostructure FeMnCoCrAl series high entropy alloy comprises the following steps: S1, forging: In this embodiment 2, (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Al9 (at.%) high entropy alloy ingot, with a mass of 16 kg, is forged into a square billet with a cross-sectional shape and size of 100 mm in width and 15 mm in thickness, and air-cooled to room temperature to obtain a forged billet; S2, warm rolling: a portion or a section of the forging blank prepared in step S1 is heated to 850°C, and the holding time is 10 min; then warm rolling is performed, and 5 passes of hot rolling are performed using a φ450 mm two-roll reversible high-strength hot rolling mill, the initial rolling temperature is 800°C, and the thickness of the forging blank is hot rolled from 15 mm to 2 mm, and after warm rolling, the forging blank is water quenched and cooled to obtain a warm rolled plate; The warm rolled plate was stretched at room temperature. According to ASTM E8 / E8M, the warm rolled annealed alloy plate was processed into a tensile specimen with a gauge length of 25 mm and a width of 6 mm by wire cutting along the rolling direction. The surface of the specimen was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimen was tested with a strain rate of 10 -3 s -1 Finally, the tensile data is processed and the engineering stress-strain curve is drawn. Figure 5 As shown in the middle figure (a), the yield strength of the warm-rolled plate is 793 MPa, the tensile strength is 846 MPa, and the elongation is 17.5%; S3, heat treatment: anneal the warm rolled sheet prepared in step S2, using a vacuum box atmosphere furnace, model KSXL-1308C, and first evacuate to 10 -3 Pa, pure argon was introduced, and then vacuum was evacuated with a vacuum pump, and pure argon was introduced again. Pure argon was introduced alternately for 3 times to ensure that a pure argon atmosphere was formed in the furnace chamber. The annealing temperature was 600 °C, and the holding time was 3 min. After the holding period, quenching was performed to obtain a warm rolled annealed high-strength heterostructure FeMnCoCrAl high-entropy alloy.

[0024] The warm-rolled annealed sample prepared in Example 2 was stretched at room temperature. According to ASTM E8 / E8M, the warm-rolled annealed alloy plate was processed into a tensile specimen with a gauge length of 25 mm and a width of 6 mm by wire cutting along the rolling direction. The surface of the specimen was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimen was subjected to a tensile test, and the strain rate was 10 -3 s -1 Finally, the tensile data was processed and the engineering stress-strain curve was drawn. The yield strength of the warm rolled annealed alloy was 804 MPa, the tensile strength was 869 MPa, and the elongation was 14.1%. Example 3

[0025] A method for preparing a high-strength heterostructure FeMnCoCrAl series high entropy alloy comprises the following steps: S1, forging: In this embodiment 3, (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Al9 (at.%) high entropy alloy ingot, with a mass of 16 kg, is forged into a square billet with a cross-sectional shape and size of 100 mm in width and 15 mm in thickness, and air-cooled to room temperature to obtain a forged billet; S2, warm rolling: a portion or a section of the forging blank prepared in step S1 is heated to 850°C, and the holding time is 10 min; then warm rolling is performed, and 5 passes of hot rolling are performed using a φ450 mm two-roll reversible high-strength hot rolling mill, the initial rolling temperature is 800°C, and the thickness of the forging blank is hot rolled from 15 mm to 2 mm, and after warm rolling, the forging blank is water quenched and cooled to obtain a warm rolled plate; S3, heat treatment: anneal the warm rolled sheet prepared in step S2, using a vacuum box atmosphere furnace, model KSXL-1308C, and first evacuate to 10 -3 Pa, pure argon was introduced, and then vacuum was evacuated with a vacuum pump, and pure argon was introduced again. Pure argon was introduced alternately for 3 times to ensure that a pure argon atmosphere was formed in the furnace chamber. The annealing temperature was 400 °C, and the holding time was 3 min. After the holding period, quenching was performed to obtain a warm rolled annealed high-strength heterostructure FeMnCoCrAl high-entropy alloy.

[0026] The warm-rolled annealed sample prepared in Example 3 was stretched at room temperature. According to ASTM E8 / E8M, the warm-rolled annealed alloy plate was processed into a tensile specimen with a gauge length of 25 mm and a width of 6 mm by wire cutting along the rolling direction. The surface of the specimen was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimen was subjected to a tensile test, and the strain rate was 10 -3 s -1 Finally, the tensile data is processed and the engineering stress-strain curve is drawn. The yield strength of the warm rolled annealed alloy is 782 MPa, the tensile strength is 834 MPa, and the elongation is 15.9%. Example 4

[0027] A method for preparing a high-strength heterostructure FeMnCoCrAl series high entropy alloy comprises the following steps: S1, forging: In this embodiment 4, (Fe 50 Mn 30 Co 10 Cr 10 ) 89 Al 11 (at.%) high entropy alloy ingot, with a mass of 16 kg, is forged to obtain a square billet with a cross-sectional shape and size of 100 mm in width × 15 mm in thickness, and air-cooled to room temperature to obtain a forging billet; S2, warm rolling: a portion or a section of the forging blank prepared in step S1 is heated to 850°C, and the holding time is 10 min; then warm rolling is performed, and 5 passes of hot rolling are performed using a φ450 mm two-roll reversible high-strength hot rolling mill, the initial rolling temperature is 800°C, and the thickness of the forging blank is hot rolled from 15 mm to 2 mm, and after warm rolling, the forging blank is water quenched and cooled to obtain a warm rolled plate; S3, heat treatment: anneal the warm rolled sheet prepared in step S2, using a vacuum box atmosphere furnace, model KSXL-1308C, and first evacuate to 10 -3 Pa, pure argon is introduced, and then vacuum is drawn with a vacuum pump, and pure argon is introduced again. Pure argon is introduced three times in an alternating cycle to ensure that a pure argon atmosphere is formed in the furnace chamber. The annealing temperature is 550℃, and the holding time is 3 min. After the holding period, quenching and cooling are performed to obtain a warm rolled annealed high-strength heterostructure FeMnCoCrAl high-entropy alloy.

[0028] The warm-rolled annealed sample prepared in Example 4 was stretched at room temperature. According to ASTM E8 / E8M, the warm-rolled annealed alloy plate was processed into a tensile specimen with a gauge length of 25 mm and a width of 6 mm by wire cutting along the rolling direction. The surface of the specimen was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimen was subjected to a tensile test, and the strain rate was 10 -3 s -1 Finally, the tensile data is processed and the engineering stress-strain curve is drawn. The yield strength of the warm rolled annealed alloy is 970 MPa, the tensile strength is 1011 MPa, and the elongation is 8.9%.

[0029] Comparative Example 1 (1) Selection of (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Al9 (at.%) high entropy alloy ingot, mass 16 Kg, forged into a cross-section of 100 × 15 mm 2 The billet is air-cooled to room temperature to obtain a forging billet; (2) The forging billet was hot rolled. The forging billet was cut and heated to 950°C. The billet was kept at this temperature for 1 h. The billet was hot rolled for 5 passes using a φ450 mm two-roll reversible high-strength hot rolling mill. The initial rolling temperature was 900°C. The thickness of the experimental alloy was hot rolled from 15 mm to 2 mm. The alloy was water quenched and cooled to obtain a hot-rolled alloy. (3) The hot-rolled plate is annealed in a vacuum box atmosphere furnace, model KSXL-1308C, and the vacuum is pumped to 10 -3 Pa, pure argon is introduced, and then vacuum is evacuated with a vacuum pump, and pure argon is introduced. This step is repeated 3 times to ensure that an argon atmosphere is formed in the furnace chamber. The annealing temperature is 550 ° C, the time is 3 min, and then quenching is performed to obtain a hot-rolled annealed high-entropy alloy.

[0030] The alloy was microstructured by electron back-scattered diffraction (EBSD). Wire cutting was used to cut samples of the hot-rolled annealed state of the high entropy alloy with a size of 10 × 10 × 2 mm. 3 The block was mechanically ground with 240#, 400#, 800#, 1000#, 1500#, 2000#, and 3000# sandpaper in sequence, and then electrolytically polished with 1:15 perchloric acid alcohol solution to remove the stress layer.

[0031] The EBSD analysis results of hot rolled samples are shown in Figure 4It shows that the sample is composed of FCC and BCC phases. Although the two phases are distributed in layers, the thickness of each layer is much greater than that of the warm-rolled sample. The FCC grains are equiaxed and elongated recrystallized, while the BCC phase is dominant (e.g. Figure 4 The two phase grains are concentrated in the state of recrystallization and slight deformation (as shown in the middle figure (a)). Figure 4 (as shown in the middle figure (b)).

[0032] The hot-rolled annealed samples were stretched at room temperature. According to ASTM E8 / E8M, the hot-rolled annealed alloy plates were processed into tensile specimens with a gauge length of 25 mm and a width of 6 mm using wire cutting along the rolling direction. The surface of the specimens was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimens were subjected to tensile testing at a strain rate of 10 -3 s -1 , and finally the tensile data is processed and the engineering stress-strain curve is drawn.

[0033] like Figure 5 The middle figure (a) shows the engineering stress-strain curve of the hot-rolled annealed alloy stretched at room temperature. The yield strength of the hot-rolled annealed alloy is 809 MPa, the tensile strength is 890 MPa, and the elongation is 13.4%. At the same time, the hot-rolled annealed sample was subjected to LUR test to evaluate the HDI stress. The true stress-true strain curve is shown in Figure 5 As shown in the middle figures (b), (c), and (d), the samples exhibit a small amount of HDI stress, which indicates that the HDI hardening effect produced by the interaction between the soft and hard domain strains is significantly smaller than that of the warm rolled annealed samples.

[0034] Comparative Example 2 (1) Selection of (Fe 50 Mn 30 Co 10 Cr 10 ) 91 Al9 (at.%) high entropy alloy ingot, mass 16 kg, forged into a cross-section of 100 × 15 mm 2 The billet is air-cooled to room temperature to obtain a forging billet.

[0035] (2) The forging billet was hot rolled. The forging billet was cut and heated to 950℃, kept warm for 1 h, and hot rolled for 5 passes using a φ450 mm two-roll reversible high-strength hot rolling mill. The initial rolling temperature was 900℃. The thickness of the experimental alloy was hot rolled from 15 mm to 2 mm, and then water quenched to obtain a hot-rolled high-entropy alloy.

[0036] The hot-rolled samples were stretched at room temperature. According to ASTM E8 / E8M, the hot-rolled alloy plates were processed into tensile specimens with a gauge length of 25 mm and a width of 6 mm by wire cutting along the rolling direction. The surface of the specimens was polished with 400# and 800# sandpaper to remove the oxide layer, prevent the clamping end from slipping with the fixture during the stretching process, and eliminate the defects on the surface of the parallel section of the specimen. The tensile specimens were subjected to tensile testing at a strain rate of 10 -3 s -1 Finally, the tensile data is processed and the engineering stress-strain curve is drawn. Figure 5 Middle figure (a). The engineering stress-strain curve of the hot-rolled alloy stretched at room temperature. The hot-rolled alloy has a yield strength of 634 MPa, a tensile strength of 710 MPa, and an elongation of 13.6%.

[0037] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a high-strength heterostructure FeMnCoCrAl high-entropy alloy, characterized in that: The following steps are involved: S1. Forging: forging the cast FeMnCoCrAl high entropy alloy raw material to obtain a forging blank; S2, warm rolling: heating the forging blank prepared in step S1 to 550°C-850°C, holding the temperature for 10 min-30 min, and then warm rolling, with a reduction rate of 10%-25% per pass and a total reduction rate of 50%-90%, and water quenching and cooling after warm rolling to obtain a warm rolled plate; S3, heat treatment: the warm rolled sheet prepared in step S2 is subjected to medium temperature annealing, the annealing temperature is 400°C to 800°C, and the holding time is 3 min to 1 h, so as to obtain a high-strength heterostructure FeMnCoCrAl series high entropy alloy.

2. The method for preparing a high-strength heterostructure FeMnCoCrAl-based high-entropy alloy according to claim 1, characterized in that: The chemical formula of the FeMnCoCrAl high entropy alloy is (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x Al x , 8≤x≤16; or in (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x Al x An FeMnCoCrAl high entropy alloy composed of interstitial elements of C, N, O and B added to a matrix, wherein the atomic percentage of the added interstitial elements of C, N, O and B is not greater than 5 at.%.

3. The method for preparing a high-strength heterostructure FeMnCoCrAl-based high-entropy alloy according to claim 2, characterized in that: The (Fe 50 Mn 30 Co 10 Cr 10 ) 100-x Al x The high entropy alloy is composed of at least two phases of FCC, BCC, HCP, B2, L12, L21, and Laves phases, and the content of a single phase is 1% to 99%.

4. The method for preparing a high-strength heterostructure FeMnCoCrAl-based high-entropy alloy according to claim 1, characterized in that: In the step S1, the cross section of the FeMnCoCrAl-based high entropy alloy forging billet is a rectangle.

5. The method for preparing a high-strength heterostructure FeMnCoCrAl-based high-entropy alloy according to claim 1, characterized in that: In step S2, the thickness of the obtained warm-rolled plate is 10 mm to 30 mm.

6. The method for preparing a high-strength heterostructure FeMnCoCrAl-based high-entropy alloy according to claim 1, characterized in that: In step S3, the warm rolled plate is heat treated and annealed in a vacuum atmosphere furnace, and the vacuum degree in the heat treatment furnace is pumped to 10 -3 Below Pa, introduce pure argon gas, then use a vacuum pump to evacuate, and introduce pure argon gas again, and alternately cycle to introduce pure argon gas for at least 3 times.

7. The method for preparing a high-strength heterostructure FeMnCoCrAl-based high-entropy alloy according to claim 1, characterized in that: In the step S3, the prepared high-strength heterostructure FeMnCoCrAl-based high-entropy alloy has a yield strength of 600 MPa to 1200 MPa, a tensile strength of 650 MPa to 1300 MPa, and an elongation of 5% to 50%.

Citation Information

Patent Citations

  • TRIP-assisted AlFeMnCoCr three-phase heterogeneous high-entropy alloy and preparation method thereof

    CN114622120A